Ambrin head honours list - Tan, Sin Chow (The Star, 2015)
GEORGE TOWN: Auditor-General Tan Sri AMbrin Buang heads the list of 1,275 people to be conferred state awards by the Yang di-Pertua Negri Tuan Abdul Rahman Abbas in conjunction with his 77th birthday today.